Long noncoding RNAs in lung cancer - Roth, Anna; Diederichs, Sven (Long Non-coding RNAs in Human Disease, 2016)
Despite great progress in research and treatment options, lung cancer remains the leading cause of cancer-related deaths worldwide. Oncogenic driver mutations in protein-encoding genes were defined and allow for personalized therapies based on genetic diagnoses. Nonetheless, diagnosis of lung cancer mostly occurs at late stages, and chronic treatment is followed by a fast onset of chemoresistance. Hence, there is an urgent need for reliable biomarkers and alternative treatment options. With the era of whole genome and transcriptome sequencing technologies, long noncoding RNAs emerged as a novel class of versatile, functional RNA molecules. Although for most of them the mechanism of action remains to be defined, accumulating evidence confirms their involvement in various aspects of lung tumorigenesis. They are functional on the epigenetic, transcriptional, and posttranscriptional level and are regulators of pathophysiological key pathways including cell growth, apoptosis, and metastasis. Long noncoding RNAs are gaining increasing attention as potential biomarkers and a novel class of druggable molecules. It has become clear that we are only beginning to understand the complexity of tumorigenic processes. The clinical integration of long noncoding RNAs in terms of prognostic and predictive biomarker signatures and additional cancer targets could provide a chance to increase the therapeutic benefit. Here, we review the current knowledge about the expression, regulation, biological function, and clinical relevance of long noncoding RNAs in lung cancer.
First online: 03 June 2015
Gesehen am 05.05.2020